Infertility Treatments and Long-Term Neurologic Morbidity of the Offspring - Levin, Shai; Sheiner, Eyal; Wainstock, Tamar; Walfisch, Asnat; Segal, Idit; Landau, Daniella; Sergienko, Ruslan; Levitas, Eliahu; Harlev, Avi (American Journal of Perinatology, 2019)
Objective To determine the risk of long-term neurologic morbidity among children (up to 18 years) born following in vitro fertilization (IVF) or ovulation induction (OI) treatments as compared with spontaneously conceived.Study Design A population-based cohort analysis was performed, including data from the perinatal computerized database on all singleton infants born at the Soroka University Medical Center (SUMC) between the years 1991 and 2014. This perinatal database was linked and cross-matched with the SUMC computerized dataset of all pediatric hospitalizations.Results Neurologic morbidity was significantly more common in IVF (3.7%) and OI (4.1%) offspring as compared with those following spontaneous pregnancies (3.1%; p = 0.017). In particular, attention deficit/hyperactivity disorders and headaches were more common in the OI group and sleep disorders in the IVF group, whereas autism and cerebral palsy were comparable between the groups. In the Weibull multivariable analysis, while controlling for maternal age, preterm delivery, birthweight centile, maternal diabetes, and hypertensive disorders, IVF (adjusted hazard ratio [HR]: 1.40; 95% confidence interval [CI]: 1.14–1.71; p = 0.001), but not OI (adjusted HR: 1.17' 95% CI: 0.92–1.48; p = 0.196), was noted as an independent risk factor for long-term pediatric neurologic morbidity.Conclusion IVF offspring appear to be at an increased risk of long-term neurologic morbidity up to 18 years of age.
Keywords: long-term pediatric neurologic morbidity; fertility treatments; in vitro fertilization; ovulation induction